2020
DOI: 10.26434/chemrxiv.13359344.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterising Lithium-Ion Electrolytes via Operando Raman Microspectroscopy

Abstract: <div><div><div><p>Knowledge of electrolyte transport and thermodynamic properties in Li-ion and ”beyond Li-ion” technologies is vital for their continued development and success. Here, we present a method for fully characterising electrolyte systems. By measuring the electrolyte concentration gradient over time via operando Raman microspectroscopy, in tandem with potentiostatic electrochemical impedance spectroscopy, the Fickian ”apparent” diffusion coefficient, transference number, the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…The concentration gradient we observe extends as far as 1.5 μm. This in agreement with previous theoretical and experimental studies which have shown electrolyte concentration gradients around electrode interfaces extending between 500 nm 84 and 10s μm 74,79,85 depending on the electrode, electrolyte composition (mass to volume ratio) and cycling conditions 86,87 .…”
Section: Visualisation Of Electrolyte Dynamicssupporting
confidence: 93%
See 1 more Smart Citation
“…The concentration gradient we observe extends as far as 1.5 μm. This in agreement with previous theoretical and experimental studies which have shown electrolyte concentration gradients around electrode interfaces extending between 500 nm 84 and 10s μm 74,79,85 depending on the electrode, electrolyte composition (mass to volume ratio) and cycling conditions 86,87 .…”
Section: Visualisation Of Electrolyte Dynamicssupporting
confidence: 93%
“…A gradient in the 2PEF intensity also becomes present above potentials of 4.0 V around LCO particles. This 2PEF/electrolyte concentration gradient, which decays quasi homogeneously away from particles, originates from the difference between the rate of delithiation at the LCO surface and the rate at which PF6anions diffuse towards the LCO particles [78][79][80][81] to balance Li + ions released and maintain electroneutraility 74,82,83 . Furthermore, at all potentials the 2PEF is relatively uniform in regions not containing LCO (bottom row) and upon discharge, the concentration gradient around particles disappears.…”
Section: Visualisation Of Electrolyte Dynamicsmentioning
confidence: 99%
“…S2.1 (ESI †) differ substantially from the measurements of Fawdon et al, who determined D from time resolved Raman microscopy. 36 Such discrepancies are often found in the literature. 6,37,38 Further work is needed to resolve such discrepancies.…”
Section: (Esi †)mentioning
confidence: 96%
“…[17][18][19][20][21][22][23] Spectroscopic techniques, capable of determining these properties for Li-ion electrolytes through direct visualisation of concentration gradients, have also recently been developed. These include X-ray spectroscopy, 24 Raman spectroscopy, 25 or magnetic resonance imaging (MRI). 26,27 However, there is currently no study which has fully characterised the ionic transport and thermodynamic properties for nonaqueous K-ion electrolytes.…”
Section: Electrolyte Characterisationmentioning
confidence: 99%
“…The trends match those found for other nonaqueous electrolytes. 16,17,25,38 With increasing concentration, first coulombic ion-ion interactions decrease the salt free energy relative to the DME, reducing the salt activity coefficient and hence causing a drop in χ M . As the concentration increases further, ion-solvent interactions increase, resulting in DME being increasingly bound, decreasing solvent vapour pressure, hence increasing the salt activity coefficient and χ M .…”
Section: Thermodynamic Factormentioning
confidence: 99%